Digital Native Characteristics: A Phenomenological Study Focused on Essential Material in Sociology Courses - Kristy, Grisyelda Tabitha; Alviani, Adistia Akses; Kusuma, Evita Rizki; Apriliana , Imroatul; Nabida, Luxnaya; Sayidina, Miastika Nur; Parahita, Bagas Narendra; Siregar, Riadi Syafutra (Jurnal Pedagogi dan Pembelajaran, 2024)
The generation of students born in the digital era (digital natives) possesses distinct characteristics that educators must consider. However, many teachers have yet to implement essential materials in their teaching practices that align with these characteristics. Therefore, teacher innovation is required to adapt and elaborate on essential materials to meet the needs of digital natives. This study aims to explore the implementation of essential sociology learning materials by teachers tailored to the characteristics of digital natives. The research employs a qualitative phenomenological approach. Data collection techniques include observation, interviews, and documentation. The study involves 14 teachers who have implemented the independent curriculum and integrated technology into the learning process, as well as 18 students actively engaged in technology-based learning from 9 high schools in the Surakarta residency. The findings reveal six characteristics of digital natives: digital proficiency, technological flexibility, experiential learning, visual orientation, social interaction, and multitasking. Teachers have made efforts to deliver essential sociology materials while considering these characteristics. However, several challenges remain, such as limited teacher proficiency in technology, lack of innovation in designing teaching media, and inadequate school facilities and infrastructure. This study contributes to helping educators adapt sociology teaching methods to the characteristics of digital natives. The findings indicate that while teachers have aligned sociology learning with the traits of digital natives, they face challenges related to infrastructure and innovation.